Hydrogel–Electrospun Fiber Mat Composite Coatings for Neural Prostheses - Han, Ning; Rao, Shreyas S.; Johnson, Jed; Parikh, Kunal S.; Bradley, Patrick A.; Lannutti, John J.; Winter, Jessica O. (Frontiers in Neuroengineering, 2011)
Achieving stable, long-term performance of implanted neural prosthetic devices has been challenging because of implantation related neuron loss and a foreign body response that results in encapsulating glial scar formation. To improve neuron-prosthesis integration and form chronic, stable interfaces, we investigated the potential of neurotrophin-eluting hydrogel-electrospun fiber mat (EFM) composite coatings. In particular, poly(ethylene glycol)-poly(ε-caprolactone) (PEGPCL) hydrogel- poly(ε-caprolactone) (PCL) EFM composites were applied as coatings for multielectrode arrays (MEAs). Coatings were stable and persisted on electrode surfaces for over 1 month under an agarose gel tissue phantom and over 9 months in a PBS immersion bath. To demonstrate drug release, a neurotrophin, nerve growth factor (NGF), was loaded in the PEGPCL hydrogel layer, and coating cytotoxicity and sustained NGF release were evaluated using a PC12 cell culture model. Quantitative MTT assays showed that these coatings had no significant toxicity toward PC12 cells, and neurite extension at day 7 and 14 confirmed sustained release of NGF at biologically significant concentrations for at least 2 weeks. Our results demonstrate that hydrogel-EFM composite materials can be applied to neural prostheses as a means to improve neuron-electrode proximity and enhance long-term device performance and function.